The Impact of Bypass Fat on Milk Contents And Yield in Indigenous Buffalo (Bubalus Bubalis) of Sindh, Pakistan - Hussain, Khalid; Azhar, Shajeela; Ali, Muhammad; Un Nisa, Qamar; Ali, Sikandar; Johar Hussain,; Fareed, Syed Khurram (BioSight, 2023)
Introduction: Buffalo and cow milk have a great affinity for strong bones, healthy teeth and in various heart diseases. The study was carried out on Kundi buffalo to assess the outcomes of bypass fat on dry matter, milk output, milk contents, body mass gain, nutrient digestibility, and production costs. Methodology: 12 buffaloes of early third and fourth lactation were selected, divided into two groups (six each) for ninety days experiment. In the test animals, additional 300 mg bypass fat was given with balance ration containing 16% of crude proteins, while in control group only balance routine ration was provided. The data was statistically evaluated using a one-way analysis of variance in a completely randomized design (CRD), and differences were assessed using a t-test. Results: The results indicated that mean values in group-A regarding the dry matter intake (DMI) was significantly elevated (P<0.05) (14.29±1.42 kg) as compared to control group (13.65 ± 2.174 kg). At the end of experiment the mean of daily milk production (7.73±1.115 liters/day) was also reported higher (P<0.05) in group-A. The milk yield of Group-A was raised up to 15.39% than the control group. Though, the buffaloes under bypass fat treatment were not found significantly higher in weight gain, but the milk contents in context of solids not fat, fat and total solids presented as P<0.05 between the treatments. Conclusion: Therefore, it is concluded from the conducted study that, bypass fat can be employed to produce milk both quantitatively and qualitatively at a reasonable cost.